Coastal Dynamics - Bosboom, Judith; Stive, Marcel J.F (Open textbook library., 2021)
This textbook on Coastal Dynamics focuses on the interrelation between physical wave, flow and sediment transport phenomena and the resulting morphodynamics of a wide variety of coastal systems. The textbook is unique in that it explicitly connects the dynamics of open coasts and tidal basins; not only is the interaction between open coasts and tidal basins of basic importance for the evolution of most coastal systems, but describing the similarities between their physical processes is highly instructive as well. This textbook emphasizes these similarities to the benefit of understanding shared processes such as nonlinearities in flow and sediment transport. Some prior knowledge with respect to the dynamics of flow, waves and sediment transport is recommended.